Prenatal Use of Sildenafil in Fetal Growth Restriction and Its Effect on Neonatal Tissue Oxygenation—A Retrospective Analysis of Hemodynamic Data From Participants of the Dutch STRIDER Trial - Terstappen, Fieke; Richter, Anne E.; Lely, A. Titia; Hoebeek, Freek E.; Elvan-Taspinar, Ayten; Bos, Arend F.; Ganzevoort, Wessel; Pels, Anouk; Lemmers, Petra M.; Kooi, Elisabeth M. W. (Frontiers in Pediatrics, 2020)
Objective: Sildenafil is under investigation as a potential agent to improve uteroplacental perfusion in fetal growth restriction (FGR). However, the STRIDER RCT was halted after interim analysis due to futility and higher rates of persistent pulmonary hypertension and mortality in sildenafil-exposed neonates. This hypothesis-generating study within the Dutch STRIDER trial sought to understand what happened to these neonates by studying their regional tissue oxygen saturation (rSO2) within the first 72 h after birth. Methods: Pregnant women with FGR received 25 mg placebo or sildenafil thrice daily within the Dutch STRIDER trial. We retrospectively analyzed the cerebral and renal rSO2 monitored with near-infrared spectroscopy (NIRS) in a subset of neonates admitted to two participating neonatal intensive care units, in which NIRS is part of standard care. Secondarily, blood pressure and heart rate were analyzed to aid interpretation. Differences in oxygenation levels and interaction with time (slope) between placebo- and sildenafil-exposed groups were tested using mixed effects analyses with multiple comparisons tests. Results: Cerebral rSO2 levels were not different between treatment groups (79 vs. 77%; both n = 14) with comparable slopes. Sildenafil-exposed infants (n = 5) showed lower renal rSO2 than placebo-exposed infants (n = 6) during several time intervals on day one and two. At 69–72 h, however, the sildenafil group showed higher renal rSO2 than the placebo group. Initially, diastolic blood pressure was higher and heart rate lower in the sildenafil than the placebo group, which changed during day two. Conclusions: Although limited by sample size, our data suggest that prenatal sildenafil alters renal but not cerebral oxygenation in FGR neonates during the first 72 post-natal hours. The observed changes in renal oxygenation could reflect a vasoconstrictive rebound from sildenafil. Similar changes observed in accompanying vital parameters support this hypothesis.